A new technique of two iliac cortical bone blocks sandwich technique for secondary alveolar bone grafting in cleft lip and palate patients - Nhan, Vo Van; Quan, Pham Nguyen (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2023)
Objectives: To describe in detail treatment procedure and outcomes of a new technique of two iliac cortical bone blocks sandwich for alveolar cleft in patients with unilateral cleft palate. Materials and methods: Based on previous techniques, our clinical experience with 32 cleft sites had confirmed the alveolar cleft bone graft outcomes and implant success with new technique of two iliac cortical bone blocks sandwich. Patient selection criteria was patients over 15 years old, patients in good health for endotracheal anesthesia, patients already had palatoplasty, patients with complete unilateral alveolar cleft, lack of permanent tooth germ in the cleft and did not receive any alveolar cleft bone graft. The patients underwent general dental treatment and pre-surgical orthodontic treatment. Any tooth extraction was performed 2 months before bone graft if necessary. All patients underwent late secondary bone grafting for alveolar cleft. This paragraph focused on introducing new technique and clinical results with follow-up time of 96 months after alveolar bone grafting. Results: After 4 to 6 months, 100% of cases showed good mucosal healing. After 4 to 6 months’ follow-up, the bone formation score I was 90.6% in 29 patients and score III was 9.4% in 3 patients. After 90 months, all 18 implants were recorded success in 15 patients remained follow-up. Conclusion: A new treatment method was suggested for patients with cleft lip and palate defect, not only to recover the function but also to meet the esthetic demand helping patients communicate confidently for community integration.